Characterization of the high-affinity anti-CTLA-4 monoclonal antibody JS007 for immune checkpoint therapy of cancer. Issue 1 (31st December 2023) - Guan, Jiawei; Liu, Hongchuan; Chai, Yan; Yu, Jie; Yao, Jian; Wang, Jing; Pan, Zhiwei; Zhang, Jing; Zhou, Yuehua; Liu, Hui; Yao, Sheng; Qi, Jianxun; et al.
ABSTRACT: Cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) is a critical inhibitory checkpoint molecule, and monoclonal antibodies (mAbs) targeting CTLA-4 that restore anti-tumor T cell immunity have achieved clinical success. Here, we report a humanized IgG1 mAb, namely JS007, with high binding affinity to CTLA-4. JS007 shows superior binding affinity and T-cell activating efficiency over ipilimumab. Moreover, it demonstrates substantial in vivo tumor suppression efficacy at low doses. The crystal structure of JS007/CTLA-4 complex (PDB: 8HIT) shows JS007 adopts a heavy-chain-dominant binding mode, and mainly contacts the BC loop, DE loop and FG loop of CTLA-4. Notably, two Tyr residues (VH-Y100 and VL-Y32) from the complementarity-determining region loops insert into the two cavities formed by the residues from the loops of CTLA-4, which may contribute to the stabilization of the binding. Comparative analysis with other anti-CTLA-4 mAbs indicates that the double "wedge-into-hole" binding mode is unique for JS007 and may be responsible for the high-affinity binding to CTLA-4. These findings have provided an important molecular understanding of the high-affinity CTLA-4 blockade mAbs and shed light on future development of agents targeting CTLA-4.